Peningkatan Sektor Informal pada Masa Pandemi Covid-19 di Kelurahan Sungai Andai Kecamatan Banjarmasin Utara Kota Banjarmasin - Yuli Apriati; Cucu Widaty; Syahlan Mattiro; Rahmat Nur (Publikasi Berkala Pendidikan Ilmu Sosial, 2021)
This research describes the increase in the informal sector during the Covid-19 pandemic in Sungai Andai Village, North Banjarmasin District, Banjarmasin City. The purpose of this research is to describe the changes regarding the increase in the informal sector during the Covid-19 pandemic in Sungai Andai Village, North Banjarmasin District, Banjarmasin City. The research method used in this research is to use qualitative research method. The research subjects in this study were the community of traders around the red light of Sungai Andai Village, North Banjarmasin District, Banjarmasin City, which was considered sufficiently supportive for the research focus.  To test the validity of the data, interviews were conducted with informants.  The results of the study show that the livelihoods of a number of people selling around the river road have changed due to the Covid-19 outbreak. People's income tends to decline when compared to income before the Covid-19 pandemic era. This is influenced by the decline in people's income, limited abilities and skills, narrow job opportunities in the formal sector, and the impact of layoffs. Based on the results of this study, it can be suggested for the community, especially traders, as informal sector actors to adapt to the social, economic, and cultural conditions that existed during the Covid-19 period.